Strategi dan Kebijakan Promosi Batik di Pasar Global - Sukmawati, Aurum Dinar; Kurniawan, Achmad Fathoni (Jurnal Transformasi Global, 2020)
Batik was first listed as an Intangible Cultural Humanity Heritage by UNESCO on October 2, 2009. As the home country for batik, Indonesia has committed to preserve and increase its popularity in the global market. These efforts are carried out through various strategies and policies to encourage the internationalization of batik, especially during the 2015-2019 period where there has been a significant decline in batik exports. This study aims to describe the strategy and government policy in encouraging the internationalization of batik in the global market. Using the Hybrid model proposed by Lei Li & Li/Tevfik Dalgic as one of the models of internationalization carried out by Small Medium Enterprises (SMEs). This model explains the stages of internationalization which include Planning, Execution, and Antecedent Phase. Based on this research, between 2015-2019, the Indonesian government has implemented various strategies and policies domestically and internationally to support batik SMEs, expand its non-traditional markets, and hold provisions on importing TPT batik and batik motifs to protect the industry. Yet, these strategies and policies were not very successfully implemented. The government efforts were still decentralized, so the strategic steps taken by various institutions and related stakeholders were not in sync. In addition, the shift in the antecedent phase to involve SMEs in every implementation of the internationalization program was also minimal.